Neuroanatomic correlates of anomia: A scoping review (2018)
Anomia is the inability to access the lexicon of names, it is one of the most common symptoms of aphasia, but it often appears as a symptom of other disorders and diseases such as Alzheimer’s. There are several studies on the anatomical bases of anomie, but they are not conclusive. The objective of this study is to identify, compile and analyze investigations that relate neuroanatomical areas with anomie. We conducted a scoping review and we selected ten articles from scientific databases (EBSCOhost and Science Direct) published during the period 2009 - 2016. It was found that there are different areas related to the denomination processes according to the phase of presentation of the anomie: before and after an intervention. In the previous moment there are the temporary and frontal gyrus in the left hemisphere, while after intervention they find activation in the temporal gyrus, precuneus, supramarginal gyrus of the right hemisphere. © Copyright Licencia creative commons Ética de publicaciones Revisión por pares Gestión por Open Journal System.